The factor structure of satisfaction ratings for selected employment concerns among people with multiple sclerosis. - Merchant, William R.; Li, Jian; Rumrill, Phillip; Roessler, Richard T.; Chan, Fong; Rumrill, Phillip D. (Journal of Vocational Rehabilitation, 2019)
OBJECTIVE: The purpose of this study was to examine the factor structure of satisfaction ratings on a collection of 38 employment concerns items among people with Multiple sclerosis (MS). RESULTS: Analyses included a cross validation to establish and confirm a factor structure. The original 38 items were reduced to 17, which were found to form three distinct factors during the calibration portion of the cross validation. These three factors were Environmental/Personal Resources, Fair Treatment, and Legal Rights, which were confirmed during the validation portion of the cross validation. CONCLUSION: It appears that the three-factor structure of these 17 items is suitable for use with individuals with MS in the evaluation of their employment-related concerns and in the subsequent delivery of rehabilitation interventions.